Local Respiratory Allergy: From Rhinitis Phenotype to Disease Spectrum - Testera-Montes, Almudena; Salas, Maria; Palomares, Francisca; Ariza, Adriana; Torres, María J.; Rondón, Carmen; Eguiluz-Gracia, Ibon (Frontiers in Immunology, 2021)
Local respiratory allergy (LRA) is defined by the negativity of atopy tests, a clinical history suggestive of airway allergy and a positive response to the nasal and/or bronchial allergen challenge. Three clinical entities have been described within LRA spectrum: local allergic rhinitis (LAR) and local allergic asthma in non-atopic individuals, and dual allergic rhinitis (coexistence of allergic rhinitis and LAR) in atopic subjects. LRA is a differentiated phenotype that does not evolve to systemic atopy over time, but which naturally progresses towards the aggravation and the association of comorbidities. Published data suggests that LRA is mediated through the mucosal synthesis of allergen-specific (s)IgE, which binds to FcεRI on the surface of resident effector cells (mast cells and basophils), and in >50% of cases traffics to the blood stream to sensitize circulating basophils. To date, 4 clinical trials have demonstrated the ability of allergen immunotherapy (AIT) to control nasal, conjunctival and bronchial symptoms, to improve quality of life, and to increase the airway tolerance to the allergen and the serum sIgG4 in LRA individuals. Collectively, these data indicate that local allergy is a relevant disease mechanisms in both atopic and non-atopic patients with airway diseases.